Pengaruh Kualitas Produk dan Desain Produk terhadap Keputusan Pembelian Produk Wardah pada Ela Kosmetik Padang - Rincel Dwi Rahayu; Lidya Martha (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of product quality and product design on purchasing decisions for Wardah products at Ela Cosmetics Padang. This type of research is quantitative, where this research uses numerical data and the research process emphasizes objective measurement of results using statistical analysis. The population in this study were consumers using Wardah products during the last 6 months, namely 660 consumers. The sampling technique used was random sampling. The number of samples was 70 people obtained using the Isaac and Michael formula. The type of data used in this research is quantitative and qualitative data. Meanwhile, the data sources are primary and secondary data sources. The data analysis technique uses multiple linear regression using the SPSS version 21.00 program. The hypothesis was tested using the t test at α = 0.05. The results of this research show that product quality and product design have a positive and significant effect on purchasing decisions for Wardah products at Ela Cosmetics Padang.